Análise das características clínica, histopatológica e imunopatológica das lesões liquenoides orais. Revisão sistemática e estudo prospectivo - Ferrisse, Túlio Morandin [UNESP] (2016)
The concept of lichenoid reaction or lichenoid interface was introduced in dermatology to define various inflammatory diseases of the skin that have similar histopathological features. Just as the skin and oral mucosa is affected by a variety of oral lichenoid lesions (OLLs). OLLs were classified as contact Lichenoides injury; drug Lichenoides injury; chronic graft versus host and not classifiable lichenoid lesions aspect lichen planus-like, such as chronic ulcerative stomatitis (CUS) recently described. Besides the overlapping features among injuries that make up this group, oral lichen planus (OLP) is the main differential diagnosis. Traditionally, the diagnosis of OLLs and the OLP depends on the clinical and histopathological association, but in many cases, this approach does not provide a confident diagnosis. The achievement of clinical and laboratory studies may help to understand the pathogenesis of these diseases and refine the ability to differentiate OLLs. Thus, the specific objectives of this study were: (1) conduct a systematic review of CUS with particular emphasis on clinical, histopathological and immunopathological of this newly described condition; and (2) Conducting a prospective study to evaluate the clinical and histopathological characteristics of OLLs.